2007
DOI: 10.1007/s00268-007-9381-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Level IIb Lymph Node Dissection Always Necessary in N1b Papillary Thyroid Carcinoma Patients?

Abstract: Introduction Papillary thyroid carcinoma (PTC) patients show a high rate of cervical lymphatic metastasis. However, there are no universal binding guidelines for the extent of lateral cervical lymph node dissection (LND) in such cases. In particular, the need for LND above the spinal accessory nerve (SAN) remains controversial. The present study examined whether level IIb lymph node (LN) dissection is always necessary in PTC patients with lateral cervical LN metastasis. Materials and Methods The study prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 40 publications
7
33
1
Order By: Relevance
“…These values are in accordance with the number of lymph nodes harvested from the hockey stick incision group (9.6, 5.6, and 29.3, respectively) and the results from a published data (mean 8.3–10.3, 6.2–6.6, and 31.1–31.5, respectively) [2224]. In addition, the mean number of metastatic lymph nodes in the transverse incision group at neck levels II and V and the total lateral compartment were 2.4, 0.4, and 5.7, respectively, which were similar to both the mean number of metastatic lymph nodes in the hockey stick incision group (2.3, 0.6, and 6.5) and the published data (1.2–2.7, 0.3–1.9, and 4.6–4.8) [2224]. These results suggest that surgical accessibility to the upper neck level is comparable between the single low transverse incision and the hockey stick incision in LND (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…These values are in accordance with the number of lymph nodes harvested from the hockey stick incision group (9.6, 5.6, and 29.3, respectively) and the results from a published data (mean 8.3–10.3, 6.2–6.6, and 31.1–31.5, respectively) [2224]. In addition, the mean number of metastatic lymph nodes in the transverse incision group at neck levels II and V and the total lateral compartment were 2.4, 0.4, and 5.7, respectively, which were similar to both the mean number of metastatic lymph nodes in the hockey stick incision group (2.3, 0.6, and 6.5) and the published data (1.2–2.7, 0.3–1.9, and 4.6–4.8) [2224]. These results suggest that surgical accessibility to the upper neck level is comparable between the single low transverse incision and the hockey stick incision in LND (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In keeping with the theory, Nogychi in a study of 68 patients after elective neck dissection, found 78% of nodal metastases in the paratracheal region and 22% in the jugular chain (Nogychi et al, 1987, as cited in Kelemen et al, 1998). Many groups have, however, reported that the risk of lymphatic metastases was greatest for the lateral nodal groups (level II, III and IV) ( Caron et al, 2006;Gimm et al, 1998;Lee et al, 2008;Roh et al, 2007Roh et al, , 2008Shah et al, 1990) while others have shown comparable rates of involvements in both the central cervical and lateral neck compartments (Machens et al, 2002).…”
Section: Lymph Nodes Metastases In Well-differentiated Thyroid Cancermentioning
confidence: 88%
“…OLNM were confined to only one level in 53% of cases, which is within the range of various reports of 32% from Kupferman et al, 39% from Pingpank et al and 64% from Ducci et al [15][16][17] in therapeutic neck dissections. Lee et al and Sivanandan et al reported a lower rate of 18% [18,19]. This wide range between studies may be explained by the geographical variability, genetic changes in the tumour tissue (ras-, gsp-,p53-and p21-mutations), accuracy in the clinical and imaging diagnosis of the N0 necks and variability of the extent of neck dissection and pathological processes [20].…”
Section: Discussionmentioning
confidence: 98%
“…Level IIb OLNM were observed in a few (2.9%) and only in cases of invasion of the surrounding levels IIa and level III. In therapeutic ND, Lee et al found a low incidence of level IIb LNM (6.8%) although a higher level of III LNM up to 80% [18]. He concluded that level IIb ND should be performed only if there is clinical or radiological evidence of metastases at this level.…”
Section: Discussionmentioning
confidence: 99%